Low cost system based on infrared technology for water management - Rojas Romero, Karin Corina (2022)
Water is an essential element in the life of the human being for which its conservation and good use is necessary, in this work we make a proposal for the development of a low-cost system for water management in order to save on Its consumption, using infrared technology, the results provide a mechanism that can be replicated and at different scales, by the use of commonly used devices.